The crystal structure of diaqua-bis(6-phenylpyridine-2-carboxylato-κ2N,O) manganese(II) — water — dimethylformamide (1/2/1), C27H31N3O9Mn - Wang Li-Hua; Tai Xi-Shi (Zeitschrift für Kristallographie - New Crystal Structures)
C27H31N3O9Mn, monoclinic, P21/n (no. 14), a = 10.8917(9) Å, b = 11.2673(16) Å, c = 23.077(3) Å, β = 93.319(10)°, V = 2827.2(6) Å3, Z = 4, Rgt(F) = 0.0735, wRref(F2) = 0.1938, T = 250 K.